Greenwashing : foundations and emerging research on corporate sustainability and deceptive communication - Vollero, Agostino (Emerald points., 2022)
Greenwashing is an emerging trend that seeks to overemphasize the sustainability practices by companies to their customers. In a comprehensive analysis of this widespread marketing and corporate communication practice, Agostino Vollero examines the understanding of greenwashing, provides a systematic review of available literature review, and reflects on theoretical approaches and research trends. Additionally explored are specific case studies that offer lessons in avoiding the greenwashing trap and a build a look to the future in this context. Greenwashing: Foundations and Emerging Research on Corporate Sustainability and Deceptive Communication showcases fascinating insights and new perspectives in this field, which will be of great interest to scholars of Management, Marketing Communications, Corporate Communication, Accounting and Business Ethics.